2020
DOI: 10.15408/etk.v19i1.11248
|View full text |Cite
|
Sign up to set email alerts
|

Is Bankruptcy Risk a Systematic Risk? Evidence from Pakistan Stock Exchange

Abstract: This study empirically investigates the relationship between default risk and cross-section of stock returns in the Pakistan Stock Exchange (PSX). Stock price data from all listed and delisted companies use to calculate monthly returns from 2001-2016. Ohlson's O-score is employed to measure exposure of firm to systematic deviation within bankruptcy risk. Besides, asset-pricing models like the Capital Asset Pricing Model (CAPM) and Fama French (FF) models are employed. Portfolios are sorted in deciles by defaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…More often, researchers turn their attention to the analysis of systematic risk. Chhapra et al (2020) describe systematic risk as 'distress risk', for these risks are caused by market fluctuations that are beyond a company's control and can be harmful to companies, placing them in financial distress. Systematic risk cannot be mitigated through diversification, as this risk originates from fluctuations in market conditions.…”
Section: Risk In Financial Perspective: Unsystematic and Systematic Riskmentioning
confidence: 99%
“…More often, researchers turn their attention to the analysis of systematic risk. Chhapra et al (2020) describe systematic risk as 'distress risk', for these risks are caused by market fluctuations that are beyond a company's control and can be harmful to companies, placing them in financial distress. Systematic risk cannot be mitigated through diversification, as this risk originates from fluctuations in market conditions.…”
Section: Risk In Financial Perspective: Unsystematic and Systematic Riskmentioning
confidence: 99%
“…Mselmi et al (2019) further explained that the absence of size and book-to-market factors led to financial distress risk becoming significant but left the proportion of return unexplained, as the model could not explain the return well. Chhapra et al (2020) investigated the relationship between default risk to represent financial distress and a cross-section of stock returns based on Pakistan's stock market using monthly returns between 2001 and 2016. They found that the stock of firms that were significantly exposed to non-diversified default risk yielded higher returns.…”
Section: Financial Distress Risk and Stock Returnmentioning
confidence: 99%
“…The pandemic acted as an environmental risk, severely impacting, and disrupting economic activities all over the world. In this regard, Chhapra, et al [17] defined systematic risk as "distress risk". The impact on the global economy is still in the process of recovery, as evidenced by persistently volatile global economic indicators and markets, high inflation rates, fluctuating commodity prices, declining GDP, and exchange rates.…”
Section: Introductionmentioning
confidence: 99%